The Effect of Different Types of Physical Exercise on the Behavioural and Physiological Parameters of Standardbred Horses Housed in Single Stalls - Barbara Padalino; Paola Zaccagnino; Pietro Celi (Veterinary Medicine International)
The aim of this study was to investigate the impacts of three different physical exercises on the physiological and behavioural patterns of Standardbred trotters housed in single stalls. Twelve racing mares were observed twice during each different exercise: daily training (DT) consisted of forty minutes at slow trot (4-5 m/s) in a small track; maximal exercise (ME) consisted of 1600 m run at maximal velocity; race (R) was a real race of 1600 m. The mares were examined at rest in their stall (Time I), soon after the completion of the exercise (Time II), one hour (Time III), and two hours (Time IV) after the exercise. Their heart rate, respiratory rate, and rectal temperature were recorded and they were videotaped in order to complete a focal animal sampling ethogram. All physiological parameters increased after exercise, in accordance with its intensity. After R and ME horses spent more time drinking, eating, and standing. The incidence of abnormal behaviours was very low and it was not affected by the different types of exercise. Overall, the assessment of horse behaviour after physical exercise by means of a focal animal sampling ethogram represents a useful tool to monitor equine welfare.